Evaluation of Corneal Endothelium in Adolescents with Juvenile Glaucoma - Beata Urban; Alina Bakunowicz-Łazarczyk; Marta Michalczuk; Małgorzata Krętowska (Journal of Ophthalmology)
Purpose. To evaluate the endothelial cell density (ECD) and central corneal thickness (CCT) in adolescents with juvenile open-angle glaucoma (JOAG) and ocular hypertension (OH) and to investigate the influence of topical antiglaucoma medications on ECD and CCT in adolescents with JOAG. Methods. ECD and CCT were investigated in 66 eyes of 33 adolescents with JOAG. Depending on the topical treatment the eyes were classified into 4 groups: (1) topical carbonic anhydrase inhibitor, (2) prostaglandin analogs, (3) beta-blocker, and (4) CAI-beta-blocker combination. ECD and CCT were also checked in 24 adolescents with OH and in control group (33 persons). Results. ECD was significantly lower in eyes with JOAG (2639.5 cells/mm2) compared with ECD in eyes with OH (2924.5 cells/mm2) and in control group (2955.5 cells/mm2). CCT was 0.554 mm in eyes with JOAG, 0.55 mm in eyes with OH, and 0.544 mm in control group. ECD in patients with JOAG was 2730 cells/mm2 (1 group), 2773.5 cells/mm2 (2 group), 2539.5 cells/mm2 (3 group), and 2551 cells/mm2 (4 group). CCT was 0.556 mm in 1 group, 0.558 mm in 2 group, 0.532 mm in 3 group, and 0.544 mm in 4 group. Conclusions. Our findings indicate that JOAG and OH did not affect CCT, but JOAG has influence on ECD in adolescents. There were no significant differences between ECD and CCT of eyes treated with different kinds of antiglaucoma medications.